What makes undergraduate students enroll into an elective course? The case of Islamic accounting - Amin, Hanudin; Abdul Rahman, Abdul Rahim; Ramayah, T. (Emerald Group Publishing, 2009)
Purpose – The main purpose of this paper is to investigate the acceptance level of Islamic accounting course by undergraduate students at the Universiti Malaysia Sabah (UMS). The study used theory of reasoned action (TRA) to analyze the findings.